TANGGUNG JAWAB MAHASISWA PENDIDIKAN JASMANI PADA PERKULIAHAN GULAT - Muhammad Fachrurrozi Bafadal; Fitriana Puspa Hidasari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Character is behavior and moral that is owned by each individual. The behavior of each individual can be formed and developed in the family, education, and community environment. The most appropriate environment and means of forming, cultivating, and developing character is the educational environment. Tanjungpura University (UNTAN) is an educational environment or higher education institution that focuses on character development, which is manifested in the Pancasila-based Character Education program which adapts the vision of the Ministry of Education and Culture. One of the important characteristics for prospective Physical Education teaches students to possess is responsibility. The purpose of this study was to see the responsibilities of physical education students in participating in wrestling lectures. This study uses a quantitative method in the form of survey research. The sample consisted of 30 students, namely students taking wrestling courses in the 2021/2022 semester. Data analysis uses a quantitative description. The results of this study indicate that 89% of students have the responsibility to carry out wrestling lectures properly and by what has been agreed upon. This study concludes that physical education students at Tanjungpura University FKIP have the responsibility to participate in and complete wrestling lectures. Students also have factors contained in responsibility, namely quality work, willingness to take risks, attachment to tasks, life goals, independence, and social engagement.